Hardened resin composition
A curable resin composition with a block polymer and crosslinking agent addresses the limitations of existing polyimide resins by enhancing heat resistance and dielectric properties, offering improved adhesiveness for electronic materials.
Patent Information
- Application Number
- JP2020191460
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-18
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2040-11-18
AI Technical Summary
Existing polyimide resins used in electronic materials lack sufficient heat resistance and dielectric properties for advanced electronic applications, and adhesives with improved solvent solubility and adhesiveness are needed for bonding and protecting circuit boards.
A curable resin composition comprising a block polymer with a polyimide unit and an ethylenically unsaturated monomer unit, combined with a crosslinking agent, which includes epoxy or phenolic hydroxyl groups to enhance heat resistance, dielectric properties, and adhesiveness.
The composition provides excellent heat resistance, dielectric properties, and high adhesiveness, suitable for use in laminates and adhesives for electronic materials, particularly in printed wiring boards.
Smart Images

Figure 0007620776000009 
Figure 0007620776000001 
Figure 0007620776000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a curable resin composition and a laminate using the same. [Background technology]
[0002] In recent years, the electronics field has seen remarkable development, particularly in the miniaturization, weight reduction, and high density of electronic devices, and electronic materials such as printed wiring boards are increasingly required to be thinner, multi-layered, and highly precise. Specific examples of adhesives and coating agents used in the periphery of such electronic materials include the following (1) to (6).
[0003] (1) Interlayer adhesive: Used to bond circuit boards together, it comes into direct contact with copper or silver circuits. It is used between the layers of multilayer boards and is available in liquid and sheet form.
[0004] (2) Adhesives for coverlay films: These are used to bond a coverlay film (such as a polyimide film used to protect the top surface of a circuit) to the underlying circuit board, and many of them have the polyimide film and adhesive layer already integrated.
[0005] (3) Copper-clad film (CCL) adhesive: Used to bond polyimide film and copper foil. Etching and other processes are performed when forming copper circuits.
[0006] (4) Coverlay: Used to protect the top surface of a circuit, it is formed by printing on the circuit (printed coverlay) or by laminating an adhesive sheet (film coverlay) and then curing it with light (photosensitive coverlay) or heat.
[0007] (5) Reinforcing plate adhesive: Used to attach part of a wiring board to a reinforcing plate made of metal, glass epoxy, polyimide, etc., in order to supplement the mechanical strength of the wiring board.
[0008] (6) Electromagnetic wave shield: Mainly consists of an adhesive conductive layer and an insulating layer, and is attached to flexible printed wiring boards for the purpose of blocking electromagnetic noise generated by electronic circuits.
[0009] These may be in the form of a liquid (made into an ink for printing) or a sheet (made into a film in advance), and the appropriate form is selected depending on the application.
[0010] In order to meet these high demands for peripheral components for electronic materials, various polyimide resins are being investigated.
[0011] On the other hand, polyimide resins have low solubility in solvents, which makes them difficult to handle. In recent years, efforts have been made to develop polyimide resins that have good solvent solubility and dielectric properties.
[0012] For example, Patent Document 1 discloses that polyimide having good solvent solubility and good dielectric properties can be synthesized by incorporating dimer diamine into polyimide. However, although the polyimide described in Patent Document 1 has high heat resistance, its dielectric properties are not sufficient for use in electronic substrates.
[0013] Patent Document 2 also discloses that the dielectric properties can be improved by using SEBS (styrene-ethylene-butylene-styrene block copolymer) modified with maleic anhydride in combination. However, the heat resistance is low and the performance is not sufficient for electronic substrates. [Prior art documents] [Patent documents]
[0014] [Patent Document 1] JP2018-168369A [Patent Document 2] Patent No. 6188788 Summary of the Invention [Problem to be solved by the invention]
[0015] An object of the present invention is to provide a curable composition having good heat resistance, good dielectric properties and high adhesion. [Means for solving the problem]
[0016] The present invention relates to the following inventions [1] to [9].
[0017] [1] A curable resin composition comprising a block polymer (C) having a polyimide unit (A) and a polymer unit (B) of an ethylenically unsaturated monomer, and a crosslinking agent (D), wherein the polymer unit (B) of the ethylenically unsaturated monomer has an epoxy group, and the crosslinking agent (D) has a phenolic hydroxyl group, or the polymer unit (B) of the ethylenically unsaturated monomer has a phenolic hydroxyl group, and the crosslinking agent (D) has an epoxy group.
[0018] [2] The curable resin composition according to [1], wherein the amount of the polymer unit (B) of an ethylenically unsaturated monomer is 10 to 50 mass % based on the total mass of the block polymer (C).
[0019] [3] The curable resin composition according to [1] or [2], wherein the glass transition temperature of the polymer unit (B) of an ethylenically unsaturated monomer is higher than the glass transition temperature of the polyimide unit (A).
[0020] [4] The curable resin composition according to any one of [1] to [3], wherein the polymer unit (B) of an ethylenically unsaturated monomer has a phenolic hydroxyl group.
[0021] [5] The curable resin composition according to any one of [1] to [4], which is an adhesive.
[0022] [6] A laminate comprising a layer made of the curable resin composition according to any one of [1] to [5] and a substrate.
[0023] [7] The laminate according to [6], wherein the substrate is a copper foil and / or an insulating sheet.
[0024] [8] A thermoset laminate obtained by heating the laminate according to [6] or [7] to thermally cure a layer made of a curable resin composition in the laminate.
[0025] [9] The thermosetting laminate according to [8], which is a printed wiring board. Effect of the Invention
[0026] According to the present invention, it is possible to provide a curable resin composition having good heat resistance, good dielectric properties and high adhesion. [Brief description of the drawings]
[0027] [Figure 1] 1 shows an infrared absorption spectrum of the block polymer obtained in Synthesis Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] The following describes in detail the embodiment of the present invention. However, the description of the constituent elements described below is one example (representative example) of the embodiment of the present invention, and the present invention is not limited to these contents as long as it does not exceed the gist of the present invention.
[0029] <Block polymer (C)> The block polymer (C) of the present invention having the polyimide unit (A) and the polymer unit (B) of an ethylenically unsaturated monomer is not particularly limited as long as the polymer unit (B) of the ethylenically unsaturated monomer contains an epoxy group or a phenolic hydroxyl group, and may have two or more types of each unit.
[0030] The block polymer may be a diblock polymer, a triblock polymer, or a multiblock polymer, but a triblock polymer is preferred because the reaction can be easily controlled.
[0031] The polyimide unit (A) constituting the block polymer can be synthesized, for example, using a known polyamic acid and a diamine, an acid dianhydride, a diisocyanate, etc. used in polyimide synthesis. The polymer unit (B) of an ethylenically unsaturated monomer can be synthesized, for example, using a known vinyl monomer such as a (meth)acrylic monomer or styrene, etc. used in vinyl polymerization.
[0032] The method of linking the polyimide unit (A) and the polymer unit (B) of an ethylenically unsaturated monomer is not particularly limited, but is preferably a linking method using an amide bond and / or an imide bond. More preferably, the polyimide unit (A) is formed by reacting the amino group of a thiol compound having an amino group with the acid anhydride group at the end of the polyimide unit (A) and radically polymerizing the polymer unit (B) of an ethylenically unsaturated monomer with the terminal thiol as a chain transfer agent as the starting point. As the thiol having an amino group, aminoethanethiol is preferred.
[0033] When an acid anhydride group is used as a linking site, the linkage between the polyimide unit (A) and the polymer unit (B) of an ethylenically unsaturated monomer is in the form of an amide bond or imide bond, which is preferable because it is chemically more stable than an ester bond or the like.
[0034] <Polyimide unit (A)> The polyimide unit (A) used in the present invention is synthesized by reacting a diamine with a polycarboxylic acid. Diamines can be roughly classified into aromatic diamines, aliphatic diamines, alicyclic diamines, and the like.
[0035] <Dimer diamine> The amine may include a dimer diamine. In the present invention, the dimer diamine is a cyclic or acyclic dimer acid obtained as a dimer of an unsaturated fatty acid, in which all the carboxyl groups have been substituted with primary amino groups. Commercially available dimer diamine products include, for example, "Priamine 1071", "Priamine 1073", "Priamine 1074", and "Priamine 1075" manufactured by Croda Japan, and "Versamin 551" manufactured by BASF Japan. The dimer diamines can be used alone or in combination of two or more.
[0036] The content of dimer diamine in the total diamines is preferably 40% by mass or more and 100% by mass or less, and more preferably 60 to 100% by mass, in order to provide excellent flexibility, adhesion, and compatibility.
[0037] The diamine used in the present invention may be a diamine other than dimer diamine. Preferred examples of the diamine other than dimer diamine include, but are not limited to, the following structures.
[0038] [ka]
[0039] [ka]
[0040] [ka]
[0041] [ka]
[0042] [ka]
[0043] <Polycarboxylic acid> The polycarboxylic acid may be in the form of an acid anhydride. Examples of the polycarboxylic acid used in the present invention include 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-diphenylethertetracarboxylic dianhydride, 4,4'-[propane-2,2-diylbis(1,4-phenyleneoxy)]diphthalic dianhydride, 2,2-bis(3,3',4,4'-tetracarboxyphenyl)tetrafluoropropane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 2,2'-bis(3,4-dicarboxyphenyl)propane dianhydride, and 2,2'-bis(3,4-dicarboxyphenyl)tetrafluoropropane dianhydride. Examples of the dianhydride include 2,2',3,3'-biphenyltetracarboxylic dianhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, pyromellitic dianhydride, 1,2,3,4-benzenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 9,9'-bis[4-(3,4-dicarboxyphenoxy)phenyl]fluorene dianhydride, 9,9'-bis(3,4-dicarboxyphenoxy)fluorene dianhydride, 1',2'-dianhydride; 4,4'-[4,4'-(propane-2,2-diyl)diphenoxy]diphthalic dianhydride, and the like. The polycarboxylic acids can be used alone or in combination of two or more kinds.
[0044] The polycarboxylic acid component is preferably at least one selected from the group consisting of 2,2-bis(3,3',4,4'-tetracarboxyphenyl)tetrafluoropropane dianhydride, 9,9'-bis[4-(3,4-dicarboxyphenoxy)phenyl]fluorene dianhydride, 1',2'-dianhydride; 4,4'-[4,4'-(propane-2,2-diyl)diphenoxy]diphthalic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, and 2,3,3',4'-biphenyltetracarboxylic dianhydride, because it has excellent compatibility with diamines, adhesion, and heat resistance.
[0045] The reaction between polycarboxylic acid and diamine can be carried out in an aprotic polar solvent by a known method. Examples of aprotic polar solvents include N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N-methyl-2-pyrrolidone (NMP), tetrahydrofuran (THF), methyldiglyme, cyclohexanone, and 1,4-dioxane. Only one type of aprotic polar solvent may be used, or two or more types may be mixed together. In this case, there is no problem in mixing the above aprotic polar solvent with a nonpolar solvent that is compatible with it, and aromatic hydrocarbons such as toluene, xylene, mesitylene, and solvent naphtha are often used. The ratio of the nonpolar solvent in the mixed solvent is preferably 30% by mass or less. This is because if the nonpolar solvent is 30% by mass or more, the dissolving power of the solvent is improved and the polyamic acid is less likely to precipitate. The reaction between the tetracarboxylic dianhydride and the diamine component is preferably carried out by dissolving the well-dried diamine component in the aforementioned reaction solvent which has been dehydrated and purified, and then adding thereto a well-dried polycarboxylic dianhydride.
[0046] The reaction between the polycarboxylic acid and the diamine may be either a random reaction or a block reaction. The reactants may be, for example, homogeneous reactants obtained by separately reacting each diamine component, or the reactants may be further reacted by recombination. For example, an acid-terminated oligomer previously prepared with an excess of polycarboxylic dianhydride and an amine-terminated oligomer previously prepared with an excess of diamine may be mixed and further reacted.
[0047] The reaction can be carried out at a relatively low temperature, for example, about 10 to 80° C., to produce a polyamic acid, which can then be thermally or chemically imidized. Alternatively, the step of producing a polyamic acid can be omitted, and the polyamic acid can be obtained by a one-step reaction of polymerization and imidization in an organic solvent at a relatively high temperature, for example, about 130 to 250° C.
[0048] Thermal imidization can be carried out at a temperature of, for example, about 200° C. to 400° C., and chemical imidization can be carried out in the presence of, for example, an organic base such as pyridine or triethylamine, and acetic anhydride, etc. The temperature at this time can be selected from any temperature range of −20 to 200° C.
[0049] A thiol compound having an amino group as a linking group can be reacted with the anhydride group at the end of the obtained polyimide unit (A). Examples of the thiol compound having an amino group include, but are not limited to, aminoethanethiol.
[0050] The reaction can be carried out at a relatively low temperature, for example, about 10 to 80° C., to produce an amic acid, which is then thermally or chemically imidized. Alternatively, the step of producing an amic acid can be omitted, and the compound can be obtained by a one-step reaction of polymerization and imidization in an organic solvent at a relatively high temperature, for example, about 130 to 250° C.
[0051] Thermal imidization can be carried out at a temperature of, for example, about 200° C. to 400° C., and chemical imidization can be carried out in the presence of, for example, an organic base such as pyridine or triethylamine, and acetic anhydride, etc. The temperature at this time can be selected from any temperature range of −20 to 200° C.
[0052] The polyimide polymer (A) obtained by thermally or chemically imidizing the polyamic acid can be used in the polymerization solution as it is in the next vinyl polymerization step. Alternatively, a poor solvent such as methanol or ethanol can be added to precipitate the resin, which can then be isolated and recovered as a powder for use in the next vinyl polymerization step.
[0053] <Polymer unit of ethylenically unsaturated monomer (B)> The polymer unit (B) of the ethylenically unsaturated monomer is synthesized by vinyl polymerization of the ethylenically unsaturated monomer. For example, in the presence of a (meth)acrylic monomer and a chain transfer agent, a radical polymerization initiator is added and a radical polymerization reaction is carried out at a reaction temperature of about 60 to 150° C., whereby the polymer unit (B) of the ethylenically unsaturated monomer having a chain transfer agent residue at its terminal can be obtained. When the polyimide unit (A) has a terminal thiol group, this acts as a chain transfer agent to form a polymer unit (B) of an ethylenically unsaturated monomer linked to the polyimide unit (A). The vinyl polymerization reaction may be carried out in the absence of a solvent, but it is preferable to use a solvent since this makes it easier to control the viscosity.
[0054] The (meth)acrylic monomer is not limited to the following examples, but may be, for example, methyl (meth)acrylic monomer. alkyl (meth)acrylates such as butyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isobutyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, myristyl (meth)acrylate, palmityl (meth)acrylate, stearyl (meth)acrylate, and behenyl (meth)acrylate; Aminoalkyl (meth)acrylates such as dimethylaminoethyl (meth)acrylate, dimethylaminopropyl (meth)acrylate, dimethylaminobutyl (meth)acrylate, diethylaminoethyl (meth)acrylate, diethylaminopropyl (meth)acrylate, dipropylaminoethyl (meth)acrylate, and dibutylaminoethyl (meth)acrylate; Aminoalkyl (meth)acrylamides such as dimethylaminoethyl (meth)acrylamide, dimethylaminopropyl (meth)acrylamide, dimethylaminobutyl (meth)acrylamide, diethylaminoethyl (meth)acrylamide, diethylaminopropyl (meth)acrylamide, dipropylaminoethyl (meth)acrylamide, and dibutylaminoethyl (meth)acrylamide; (Meth)acrylates having an alkylene oxide chain, such as polyalkylene glycol mono(meth)acrylate monoalkyl ether; Polydimethylsiloxane (meth)acrylates such as product names Silaplane FM-0711 and Silaplane FM-0721 (both manufactured by Chisso Corporation); Fluorine-containing (meth)acrylates such as product names Cheminox FAAC-4, Cheminox FAAC-6, Cheminox FAMAC-4, and Cheminox FAMAC-6 (all manufactured by Unimatec Corporation), R-1110, R-1210, R-1420, R-1620, R-5210, R-5410, R-5610, M-1110, M-1210, M-1420, M-1620, M-5210, M-5410, and M-5610 (all manufactured by Daikin Corporation), Light Acrylate FA-108 (manufactured by Kyoeisha Chemical Co., Ltd.), Viscoat-3F, Viscoat-3FM, Viscoat-4F, Viscoat-8F, and Viscoat-8FM (all manufactured by Osaka Organic Chemical Industry Co., Ltd.); vinyl copolymerization macromonomers such as Macromonomer AB-6 (butyl (meth)acrylate macromonomer), Macromonomer AW-6S (isobutyl (meth)acrylate macromonomer), Macromonomer AS-6 (styrene macromonomer), Macromonomer AN-6S (styrene / acrylonitrile macromonomer), Macromonomer AK-5 (dimethylsiloxane macromonomer) (all manufactured by Toagosei Co., Ltd.); (meth)acrylic acid polymer type (meth)acrylates such as Viscoat #150D (tetrahydrofurfuryl alcohol oligoacrylate) and Viscoat #190D (ethoxydiethylene glycol oligoacrylate) (all manufactured by Osaka Organic Chemical Industry Co., Ltd.); Examples of (meth)acrylates include benzyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, ethyl carbitol (meth)acrylate, butoxyethyl (meth)acrylate, and cyanoethyl (meth)acrylate. In addition to these, radically polymerizable vinyl monomers such as styrene and vinyl acetate can also be used. From the viewpoint of dielectric properties, the ethylenically unsaturated monomer preferably contains styrene. These ethylenically unsaturated monomers can be appropriately selected according to the purpose of use, and one type may be used alone, or two or more types may be used in combination.
[0055] The polymer unit (B) of the ethylenically unsaturated monomer is required to have a thermal crosslinking group, such as an epoxy group or a phenolic hydroxyl group, from the viewpoint of dielectric properties. The vinyl polymerization is carried out using an ethylenically unsaturated monomer that contains a thermal crosslinking group that is polymerizable with the ethylenically unsaturated monomer because it has an epoxy group or a phenolic hydroxyl group. Examples of the ethylenically unsaturated monomer having an epoxy group include glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate glycyl diether, 3,4-epoxybutyl (meth)acrylate, 3-methyl-3,4-epoxybutyl (meth)acrylate, 3-ethyl-3,4-epoxybutyl (meth)acrylate, 4-methyl-4,5-epoxypentyl (meth)acrylate, 5-methyl-5,6-epoxyhexyl (meth)acrylate, α-ethyl glycidyl acrylate, allyl glycidyl ether, crotonyl glycidyl ether, (iso)crotonic acid glycidyl ether, (3,4-epoxycyclohexyl)methyl (meth)acrylate, N-(3,5-dimethyl-4-glycidyl)benzyl a Examples of the ethylenically unsaturated monomer having a phenolic hydroxyl group include acrylamide, o-vinylbenzyl glycidyl ether, m-vinylbenzyl glycidyl ether, p-vinylbenzyl glycidyl ether, α-methyl-o-vinylbenzyl glycidyl ether, α-methyl-m-vinylbenzyl glycidyl ether, α-methyl-p-vinylbenzyl glycidyl ether, 2,3-diglycidyloxymethylstyrene, 2,4-diglycidyloxymethylstyrene, 2,5-diglycidyloxymethylstyrene, 2,6-diglycidyloxymethylstyrene, 2,3,4-triglycidyloxymethylstyrene, 2,3,5-triglycidyloxymethylstyrene, 2,3,6-triglycidyloxymethylstyrene, 3,4,5-triglycidyloxymethylstyrene, and 2,4,6-triglycidyloxymethylstyrene.Specific examples of the ethylenically unsaturated monomer having a phenolic hydroxyl group include (meth)acrylic acid=4-hydroxyphenyl, (meth)acrylamide=4-hydroxyphenyl, and 4-maleimidephenol. These monomers can be appropriately selected depending on the purpose of use, and one type may be used alone, or two or more types may be used in combination. From the viewpoint of dielectric properties, polymer units of ethylenically unsaturated monomers having a phenolic hydroxyl group, such as (meth)acrylic acid=4-hydroxyphenyl, (meth)acrylamide=4-hydroxyphenyl, and 4-maleimidophenol, are preferred, and 4-maleimidophenol is more preferred. The content of the ethylenically unsaturated monomer having a thermal crosslinking group, such as an epoxy group or a phenolic hydroxyl group, is preferably 1 to 50 mass % of the total monomers, and more preferably 1 to 30 mass %, from the viewpoints of heat resistance, adhesion, and dielectric properties.
[0056] Examples of the polymerization initiator include organic peroxides such as benzoyl peroxide, tert-butyl perbenzoate, cumene hydroperoxide, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di(2-ethoxyethyl)peroxydicarbonate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxyneodecanoate, tert-butyl peroxypivalate, (3,5,5-trimethylhexanoyl)peroxide, dipropionyl peroxide, and diacetyl peroxide; and 2,2' Examples of the azo-based compounds include azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane 1-carbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile), dimethyl 2,2'-azobis(2-methylpropionate), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-hydroxymethylpropionitrile), and 2,2'-azobis[2-(2-imidazolin-2-yl)propane]. These polymerization initiators may be used alone or in combination of two or more.
[0057] Examples of the solvent include, but are not limited to, acetone, methyl ethyl ketone, cyclohexanone, methyl acetate, ethyl acetate, propyl acetate, toluene, xylene, anisole, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, N-vinylpyrrolidone, N-methylcaprolactam, dimethylsulfoxide, tetramethylurea, pyridine, dimethylsulfone, hexamethylsulfoxide, m-cresol, γ-butyrolactone, γ-valerolactone, etc. These solvents may be used alone or in combination of two or more.
[0058] <Glass transition temperature> In the block polymer (C) of the present invention, the glass transition temperatures of the polyimide unit (A) and the polymer unit (B) of the ethylenically unsaturated monomer can be controlled by the monomer used. In addition, this type of block polymer forms a phase-separated structure when a coating film is formed. The presence of a part (soft) with a low glass transition temperature and a part (hard) with a high glass transition temperature in each of the separated layers allows both interface adhesion and cohesive strength to be achieved, thereby providing strong adhesion to the substrate. This is also applied in the present invention, and for example, by lowering the glass transition temperature of the polyimide unit (A) and increasing the glass transition temperature of the polymer unit (B) of the ethylenically unsaturated monomer, it is possible to form a phase-separated structure in which the soft part composed of the polyimide unit (A) and the hard part composed of the polymer unit (B) of the ethylenically unsaturated monomer are separated. In the present invention, since the polymer unit (B) of the ethylenically unsaturated monomer has a crosslinked part, it is preferable to increase the glass transition temperature of the polymer unit (B) of the ethylenically unsaturated monomer and decrease the glass transition temperature of the polyimide unit (A).
[0059] <Crosslinking agent (D)> The curable composition of the present invention further contains a crosslinking agent (D) for improving heat resistance and adhesiveness. Examples of the crosslinking agent include an epoxy group-containing compound and a phenolic hydroxyl group-containing compound.
[0060] <Epoxy group-containing compounds> The epoxy group-containing compound used in the present invention may be any compound having an epoxy group in the molecule, and is not particularly limited, but preferably has an average of two or more epoxy groups in one molecule. As the epoxy group-containing compound, for example, an epoxy resin such as a glycidyl ether type epoxy resin, a glycidyl amine type epoxy resin, a glycidyl ester type epoxy resin, or a cyclic aliphatic (alicyclic) epoxy resin can be used.
[0061] Examples of the glycidyl ether type epoxy resin include cresol novolac type epoxy resin, phenol novolac type epoxy resin, and tetrakis(glycidyloxyphenyl)ethane. Examples of such epoxy resins include N,N,N',N'-tetraglycidyl-1,3-benzenedi(methanamine), tetraglycidyl diaminodiphenylmethane, tetraglycidyl metaxylylenediamine, 1,2,4-benzenetricarboxylic acid triglycidyl ester, 1,3,5-benzenetricarboxylic acid triglycidyl ester, 1,1,2,4,5-benzenetetracarboxylic acid tetraglycidyl ester, tri(carboxyethyl)isocyanurate triglycidyl ester, polyglycidyl esters derived from polycarboxylic acids such as polymerized fatty acids, cyclohexane-1,2,4-tricarboxylic acid triglycidyl ester, 1,2,4-cyclohexanetricarboxylic acid triglycidyl ester, 1,3,5-cyclohexanetricarboxylic acid triglycidyl ester, 2,4,5-cyclohexanetetracarboxylic acid tetraglycidyl ester, bisphenol A type epoxy resin, bisphenol F type epoxy resin, and dicyclopentadiene type epoxy resin. Further examples include diglycidyl phthalate, diglycidyl hexahydrophthalate, diglycidyl tetrahydrophthalate, 3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexane carboxylate, and the like.
[0062] <Phenol-containing hydroxyl group compounds> The crosslinking agent having a phenolic hydroxyl group may be a monomer compound or a polymer compound. The crosslinking agent having a phenolic hydroxyl group, which is a polymer compound, may be a polymer (homopolymer) of a single monomer or a copolymer (copolymer) of multiple types of monomers. In addition, the crosslinking agent having a phenolic hydroxyl group may be any of a random copolymer, a block copolymer, or a graft copolymer.
[0063] Examples of crosslinking agents having a phenolic hydroxyl group include bisphenol A, bisphenol F, bisphenol S, resorcin, catechol, hydroquinone, fluorene bisphenol, 4,4'-biphenol, 4,4',4"-trihydroxytriphenylmethane, naphthalene diol, 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane, calixarene, novolak-type phenolic resins (e.g., polyhydric phenol novolak resins synthesized from polyhydric hydroxy compounds and formaldehyde, such as phenol novolak resins, cresol novolak resins, bisphenol A novolak resins, bisphenol S novolak resins, and resorcin novolak resins), naphthol-phenol co-condensed novolak resins, naphthol-cresol co-condensed novolak resins, naphthol novolak resins, and alkanol. Examples of polyhydric phenol compounds include polyhydric phenol compounds such as alkoxy group-containing aromatic ring-modified novolak resins (polyhydric phenol compounds in which a phenol nucleus and an alkoxy group-containing aromatic ring are linked by formaldehyde)), aralkyl-type phenol resins (for example, phenol aralkyl resins such as Xylok resin and naphthol aralkyl resins), aromatic hydrocarbon formaldehyde resin-modified phenol resins, dicyclopentadiene phenol addition type resins, trimethylolmethane resins, tetraphenylolethane resins, biphenyl-modified phenol resins (polyhydric phenol compounds in which a phenol nucleus is linked by a bismethylene group), biphenyl-modified naphthol resins (polyhydric naphthol compounds in which a phenol nucleus is linked by a bismethylene group), and aminotriazine-modified phenol resins (polyhydric phenol compounds in which a phenol nucleus is linked by melamine, benzoguanamine, or the like).
[0064] Specific examples of novolac-type phenolic resins include "Phenolite TD-2131" and "Phenolite TD-2090" (trade names) manufactured by DIC Corp. Specific examples of aralkyl-type phenolic resins include GPH-65 (trade name) manufactured by Nippon Kayaku Co., Ltd.
[0065] From the viewpoint of durability and adhesiveness, the content of the epoxy resin or the phenolic hydroxyl group-containing compound is preferably 1 to 30 parts by mass, and more preferably 1 to 20 parts by mass, per 100 parts by mass of the block polymer (C).
[0066] <Other additives> The curable composition of the present invention may further contain additives such as antioxidants, ultraviolet absorbers, hydrolysis inhibitors, antifungal agents, thickeners, plasticizers, pigments, and fillers as necessary, and may also contain known catalysts, additives, etc. for adjusting the curing reaction.
[0067] <Adhesive, adhesive layer> The curable composition of the present invention can be in the form of an adhesive. The adhesive is for bonding two objects, the same or different, as described in the Background Art section. In many cases, the adhesive is preferably a thermosetting or photosetting adhesive, in order to achieve both convenience in forming an adhesive layer and strong adhesive strength after the adhesive layer is formed. The adhesive can be an adhesive obtained by mixing the block polymer (C) with a resin alone, a curing agent, a filler, an additive, etc., in any ratio. For example, the adhesive can be obtained by applying the adhesive to a suitable support film, curing the adhesive by heating to volatilize the organic solvent, and peeling it off from the support film. The thickness of the adhesive layer is preferably about 3 μm or more and 40 μm or less.
[0068] When producing the adhesive layer, the above adhesive may be used in combination with various known adhesives other than the above adhesive.Similarly, the above adhesive may be used in combination with various known adhesives other than the above adhesive.
[0069] The adhesive can also be used as an adhesive sheet by impregnating a fiber substrate, semi-curing (B-stage) by heating or the like, laminating it on a metal foil or plastic film, and curing it. As the fiber substrate, well-known materials used in various laminates for electrical insulating materials can be used. Examples of the material include inorganic fibers such as E-glass, S-glass, low dielectric glass, and Q-glass; organic fibers such as low dielectric glass polyimide, polyester, and tetrafluoroethylene; and mixtures thereof. In particular, from the viewpoint of dielectric properties, inorganic fibers are preferred, and low dielectric glass and Q-glass are more preferred. When the adhesive of the curable composition of the present invention is impregnated into a fiber substrate, which is a support film, the adhesive forms a continuous adhesive layer, resulting in a form in which the substrate is included within the adhesive layer, which is one of the usage forms of the curable composition of the present invention. Of course, the adhesive sheet may be a laminate in which the sheet-like substrate and the adhesive layer are independent of each other.
[0070] <Laminate> The laminate of the present invention is a laminate in which a polyimide resin adhesive, a film-like adhesive, or an adhesive sheet is laminated between at least two substrates. For example, it can be used when laminating a copper foil and a support film such as polyimide. For example, it is a laminate in which an adhesive layer is formed on a first substrate using an electronic material that is the adhesive of the present invention, or a laminate in which a second substrate is further laminated on the adhesive layer. The substrate is not particularly limited and may be, for example, a sheet or plate-like substrate, and may include conventionally known plastic films, metal foils, etc. When two substrates are used, they may be the same or different. In the present invention, the heat-cured laminate is also referred to as a thermoset laminate.
[0071] <Adhesive sheet> When the substrate is a support film and the layer made of the curable resin composition is an adhesive layer, it is also called an adhesive sheet. Note that, even when the adhesive is impregnated into the substrate and there is no laminated structure, or when the adhesive can maintain the sheet shape without a substrate, it may be called an adhesive sheet as long as it has adhesive properties. The adhesive sheet of the present invention can be obtained, for example, as follows. A thermosetting adhesive in a solution or dispersion state can be applied to at least one side of a support film and then dried, usually at 40 to 150° C., to obtain a thermosetting adhesive sheet in an uncured state (so-called B-stage state) with a sheet-like substrate attached thereto. The other side of the thermosetting adhesive sheet can then be covered with another sheet-like substrate to obtain the thermosetting adhesive sheet with a support film of the present invention. At least one of the support films used is preferably a peelable support film. That is, a thermosetting adhesive in a solution or dispersion state is applied to a peelable support film and dried to form a thermosetting adhesive sheet, and then the other side of the thermosetting adhesive sheet can be covered with another peelable support film or a non-peelable support film that serves as an adherend.
[0072] When the adhesive is thermosetting, the adhesive sheet using it is also called a thermosetting adhesive sheet. Also, the layer made of the adhesive is called a thermosetting adhesive layer. Thermosetting refers to hardening at a temperature of about 40 to 200°C.
[0073] The following describes the case where a thermosetting adhesive sheet with a peelable substrate is used, in which one side of the thermosetting adhesive sheet is covered with a peelable substrate and the other side is covered with a sheet-like substrate (e.g., a polyimide film or a polyester film). The release substrate is peeled off from the thermosetting adhesive sheet with the release substrate. An adherend (for example, the circuit surface side of a printed wiring board having a conductive circuit) is placed on the exposed thermosetting adhesive layer. Next, the thermosetting adhesive layer sandwiched between the sheet-like substrate and the adherend is thermally cured by applying heat and pressure, and the thermosetting adhesive layer becomes a sheet-like cured product. In this way, the front surface of a printed wiring board having a conductive circuit can be formed through the sheet-like cured product. A printed wiring board with a protective sheet can be obtained in which the circuit surface is protected with a sheet-like base material (protective sheet). At least one of the support films used is preferably a peelable support film. That is, a thermosetting adhesive in a solution or dispersion state is applied to a peelable support film and dried to form a thermosetting adhesive sheet, and then the other side of the thermosetting adhesive sheet can be covered with another peelable support film, or can be covered with a non-peeling support film that serves as an adherend. Alternatively, a thermosetting adhesive in a solution or dispersion state can be applied to a non-peeling support film that serves as an adherend and dried to form a thermosetting adhesive sheet, and then the other side of the thermosetting adhesive sheet can be covered with another peelable sheet-like substrate.
[0074] The dry film thickness of the thermosetting adhesive sheet is preferably 5 to 500 μm, more preferably 10 to 100 μm, in order to ensure sufficient adhesiveness and solder heat resistance, and from the standpoint of ease of handling. Examples of the coating method include comma coating, knife coating, die coating, lip coating, roll coating, curtain coating, bar coating, gravure printing, flexographic printing, dip coating, spray coating, and spin coating.
[0075] <Support film> Among the support films that can be used, those having no peelability include various plastic films, such as polyimide films, polyester films, polyphenylene ether films, polyphenylene sulfide films, polystyrene films, polycarbonate films, and polyether ether ketone films. Among the support films used, those having releasability include various plastic films that have been subjected to a release treatment, paper that has been subjected to a release treatment, etc. Examples of various plastic films that can be subjected to the release treatment include polyester films and polyolefin films.
[0076] Next, a case where a thermosetting adhesive sheet with a release substrate, in which both sides of a thermosetting adhesive sheet are covered with two release substrates, will be described. One of the release substrates is peeled off from the thermosetting adhesive sheet with the release substrate. An adherend (e.g., a polyimide film or a polyester film) is placed on the exposed thermosetting adhesive layer. The other release substrate that covered the other side of the thermosetting adhesive layer is peeled off. Another adherend (e.g., the circuit surface side of a printed wiring board having a conductive circuit) is placed on the exposed thermosetting adhesive layer. Next, the thermosetting adhesive layer sandwiched between the two adherends is thermally cured by applying heat and pressure. After the circuit surface side of a printed wiring board having a conductive circuit is placed on the surface from which the release substrate was first peeled off, a polyimide film or a polyester film can also be placed on the other side of the thermosetting adhesive layer.
[0077] An example of a printed wiring board laminate having a conductive circuit (hereinafter also referred to as a wiring board) is a flexible printed wiring board in which a conductive circuit is formed on a flexible, insulating plastic film such as polyester or polyimide. As a method for providing a conductive circuit, for example, a photosensitive etching resist layer can be formed on the copper foil of a flexible copper-clad board, which is made by providing copper foil on a base film with or without an adhesive layer, exposing it to light through a mask film having a circuit pattern to harden only the exposed areas, and then removing the copper foil in the unexposed areas by etching, and then peeling off the remaining resist layer, thereby forming a conductive circuit from the copper foil. Alternatively, only the necessary circuits may be provided on a base film by means of sputtering, plating, or the like. Alternatively, a conductive ink containing silver or copper particles may be used to form a conductive circuit on a base film by a printing technique.
[0078] <Multi-layer flexible printed wiring> The thermosetting adhesive sheet of the present invention is preferably used for producing a printed wiring board with a protective sheet, and can also be used as follows. A multilayer flexible printed wiring board can also be obtained by sandwiching the thermosetting adhesive sheet of the present invention between a plurality of flexible printed wirings and curing the thermosetting adhesive sheet by applying heat and pressure.
[0079] <Laminating base film and copper foil for flexible printed wiring boards> For example, the thermosetting adhesive sheet of the present invention can be sandwiched between a polyimide film and a copper foil, and the thermosetting adhesive sheet can be cured by applying heat and pressure.
[0080] <Conductive adhesive sheet> The thermosetting adhesive sheet of the present invention can be used as a conductive thermosetting adhesive sheet formed by dispersing a thermosetting composition containing a polyimide resin, a curing agent, a specific amount of an alkali metal compound, and a conductive metal filler such as copper or silver, or a conductive filler such as carbon, in the form of a sheet.
[0081] <Electromagnetic wave shield> Furthermore, the thermosetting adhesive sheet of the present invention can be used as an electromagnetic wave shield by forming a multilayer structure with an insulating layer using the conductive thermosetting adhesive sheet prepared above. In addition to the conductive layer portion, the thermosetting adhesive sheet of the present invention can also be used as an insulating layer.
[0082] <Thermal conductive adhesive sheet> Furthermore, the thermosetting adhesive sheet of the present invention can be used as a thermally conductive thermosetting adhesive sheet obtained by dispersing and blending a polyimide resin, a curing agent, a specific amount of an alkali metal compound, and a thermally conductive inorganic filler, a metal filler, etc., and forming the dispersed thermosetting composition into a sheet shape. EXAMPLES
[0083] The present invention will be described in more detail below with reference to examples and comparative examples. In the examples and comparative examples, parts and % mean parts by mass and % by mass unless otherwise specified.
[0084] <Method of measuring number average molecular weight (Mn) and mass average molecular weight (Mw)> The measurements of Mn and Mw were performed using a GPC (gel permeation chromatography) "HPC-8020" manufactured by Tosoh Corporation. GPC is a liquid chromatography that separates and quantifies substances dissolved in a solvent (THF; tetrahydrofuran) based on the difference in their molecular size. The measurements in the present invention were performed using two "LF-604" columns (manufactured by Showa Denko K.K.: GPC column for rapid analysis: 6 mm ID x 150 mm size) connected in series, at a flow rate of 0.6 ml / min and a column temperature of 40°C, and the number average molecular weight (Mn) and mass average molecular weight (Mw) were determined in terms of polystyrene.
[0085] <Method of measuring infrared absorption spectrum> The infrared absorption spectrum was measured using a NICOLET iS5 ATR manufactured by Thermo Science Co., Ltd. The sample used was a free film (film thickness: about 25 microns) of the synthesized resin.
[0086] <Measurement of glass transition temperature Tg> The obtained adhesive sheet was measured using a Shimadzu Corporation "Differential Scanning Calorimeter DSC-60 PLUS" under conditions of a starting temperature of 25°C, an ending temperature of 250°C, and a heating rate of 10.0°C / min, using 10 mg of sample, and after the first heating, it was rapidly cooled to the starting temperature, and the peak value measured at the second cycle under the same conditions was measured. Two Tg values were observed that were thought to be derived from each of the components (A) and (B) of the block polymer, with Tg1 indicating the glass transition point that was thought to be derived from the polyimide unit (A), and Tg2 indicating the glass transition point that was thought to be derived from the polymer unit (B) of the ethylenically unsaturated monomer.
[0087] The abbreviations of the compounds used in the examples are as follows. DDA: Product name: Priamine 1075 (manufactured by Croda Japan) BAPP: 4,4'-isopropylidenebis[(4-aminophenoxy)benzene] (manufactured by Seika Chemical Co., Ltd.) BISDA: 1',2'-dianhydride; 4,4'-[4,4'-(propane-2,2-diyl)diphenoxy]diphthalic dianhydride, manufactured by SABIC Japan 6FDA: 2,2-bis(3,3',4,4'-tetracarboxyphenyl) manufactured by Wakayama Seika Kogyo Co., Ltd. St: styrene StMA: Stearyl methacrylate MAA: Methacrylic acid MA: Maleic anhydride PhOHMA: 4-hydroxyphenyl methacrylate PhOHMAm: Methacrylamide = 4-hydroxyphenyl MAPh: 4-maleimidophenol GMA: glycidyl methacrylate Tuftec M1913: Hydrogenated styrene-based thermoplastic elastomer (SEBS) (manufactured by Asahi Kasei Corporation) TETRAD-X: Epoxy compound (manufactured by Mitsubishi Gas Chemical Company, tetrafunctional glycidylamine compound) Phenolite TD-2131: Novolac type phenolic resin (manufactured by DIC)
[0088] (Synthesis Example 1) Synthesis of polyimide unit (A-1) In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping tank and a nitrogen gas inlet tube, 240 parts of DMF and 46.8 parts of 6FDA were charged, and the temperature was raised to 100°C while stirring under a nitrogen stream. 53.2 parts of DDA were dropped over 1 hour, and then the temperature was raised to 140°C and a dehydration reaction was carried out for 14 hours, and the temperature was further raised to 180°C to remove the solvent, thereby obtaining a polyimide unit (A-1) having a number average molecular weight of about 17,000 and a mass average molecular weight of about 38,200. The resin solid content concentration was 60%.
[0089] (Synthesis Examples 2 to 3) Synthesis of polyimide units (A-2) and (A-3) Polyimide units (A-2) and (A-3) were obtained in the same manner as in Synthesis Example 1, except that the monomers shown in Table 1 were used. The Mn, Mw and Tg of the obtained polyimide resins are shown in Table 1.
[0090] (Synthesis Example 4) Synthesis of Block Polymer (C-1) In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping tank and a nitrogen gas inlet tube, 100 parts of polyimide unit (A-1) and 0.75 parts of 2-aminoethanethiol were charged, and the temperature was raised to 100°C while stirring under a nitrogen stream. After 2 hours, the temperature was raised to 140°C, and a dehydration reaction was carried out for 14 hours, and the mixture was cooled to room temperature. Then, 30.8 parts of styrene and 5.2 parts of 4-maleimidophenol were charged and the temperature was raised to 100°C. After the temperature was raised, 0.36 parts of AIBN were added and the mixture was reacted for 7 hours. Then, a solvent was appropriately added to obtain a block polymer (C-1) having a number average molecular weight of about 18,500 and a mass average molecular weight of about 46,500. The resin solid content was 50%.
[0091] (Synthesis Examples 5 to 13) Synthesis of Block Polymers (C-2 to C-10) Polyimide units (C-2) to (C-10) were obtained in the same manner as in Synthesis Example 4, except that the polyimide units and monomers shown in Table 2 were used. Table 2 shows Mn, Mw, Tg1, and Tg2 of the obtained block polymers.
[0092] [Example 1] 50 parts of the block polymer (C-1) obtained in Synthesis Example 1, 1.5 parts of TETRAD-X, and 20 parts of toluene were mixed and stirred to prepare a curable resin composition. The curable resin composition was uniformly coated on a polyester film that had been peeled off using a blade coater so that the film thickness after drying was 50 μm, and then dried to obtain a laminate. After that, the laminate was heated in a hot air oven at 180° C. for 1 hour, and then the film-like polyimide resin was peeled off from the polyester film after drying to obtain an adhesive sheet that is a thermosetting laminate. [Examples 2 to 7, Comparative Examples 1 to 5] An adhesive sheet was obtained in the same manner as in Example 1, except that the materials and amounts thereof shown in Table 3 were used.
[0093] (Evaluation of relative dielectric constant) Three test pieces were set in an ADMS01Oc dielectric constant measuring device manufactured by AET Corporation, and the dielectric constant was determined using the cavity resonator method at a measurement temperature of 23°C and a measurement frequency of 10 GHz, and evaluated according to the following criteria. A: Dielectric constant less than 2.7 (very good) B: Dielectric constant 2.7 or more and less than 2.8 (good) C: Dielectric constant 2.8 or more and less than 3.1 (usable) D: Dielectric constant 3.1 or more (unusable)
[0094] (Evaluation of dielectric tangent) Three test pieces were set in an ADMS01Oc dielectric constant measuring device manufactured by AET Corporation, and the dielectric loss tangent was determined using the cavity resonator method at a measurement temperature of 23°C and a measurement frequency of 10 GHz, and evaluated according to the following criteria. A: Dielectric tangent less than 0.005 (very good) B: Dielectric tangent 0.005 or more and less than 0.007 (good) C: Dielectric tangent 0.007 or more and less than 0.015 (usable) D: Dielectric tangent 0.015 or more (unusable) <Adhesiveness> The thermosetting resin sheet with one-sided release film prepared in the above glass transition temperature measurement test was cut into a size of 65 mm x 65 mm, and after removing the release film, it was sandwiched between 75 μm thick polyimide films [Toray DuPont Co., Ltd. "Kapton 300H"] and laminated at 80 ° C., and then pressure-bonded for 30 minutes at 180 ° C. and 1.0 MPa. Furthermore, this test piece was thermally cured at 180 ° C. for 1 hour to prepare a test piece for evaluation. This test piece was cut into a width of 10 mm and a length of 65 mm, and a T-peel peel test was performed at a pulling speed of 300 mm / min in an atmosphere of 23 ° C. and 50% relative humidity to measure the adhesive strength (N / cm). This test evaluates the adhesive strength of the adhesive layer when used at room temperature, and the results were judged according to the following criteria. A..."10(N / cm)<adhesion strength" B..."6(N / cm)<adhesion strength≦10(N / cm)" C..."3(N / cm)<adhesion strength≦6(N / cm)" D... "Adhesive strength ≦ 3 (N / cm)" <Long-term heat resistance> As in the above adhesion test, test pieces cut to a width of 10 mm and a length of 65 mm were stored in an air atmosphere at 150°C for over 1000 hours, and then removed and their adhesive strength was measured. The degree of decrease in adhesive strength from that at room temperature was confirmed, and the results were judged according to the following criteria. A: The adhesive strength decreases by less than 20% compared to the adhesive strength at room temperature. B: The percentage decrease in adhesive strength compared to the adhesive strength at room temperature is 20% or more but less than 50%. C: The percentage decrease in adhesive strength compared to the adhesive strength at room temperature is between 50% and 80%. D: The adhesive strength is reduced by 80% or more compared to the adhesive strength at room temperature.
[0095] As shown in Table 3, the adhesive sheet obtained from the thermosetting composition of the present invention has excellent dielectric properties such as dielectric constant and dielectric tangent, as well as high adhesion and long-term heat resistance. In particular, Examples 1 to 8 having block polymers (A-1) to (A-7) in which a polyimide unit (A) and an ethylenically unsaturated monomer polymer unit (B) are linked showed excellent dielectric properties, adhesion and long-term heat resistance. Among them, Examples 1 to 6 having (A-1) to (A-6) in which the ethylenically unsaturated monomer polymer unit (B) has a phenolic hydroxyl group were excellent overall in terms of dielectric properties, adhesion and long-term heat resistance. Furthermore, among them, (C-1), (C-2) and (C-3) in which the ethylenically unsaturated monomer polymer unit (B) has styrene and a maleimide group-containing phenolic hydroxyl group were particularly excellent in dielectric properties.
[0096] [Table 1]
[0097] [Table 2]
[0098]
Table 3
Claims
1. A curable resin composition comprising a block polymer (C) having a polyimide unit (A) and a polymer unit (B) of an ethylenically unsaturated monomer, and a crosslinking agent (D), The polyimide unit (A) is a reaction product of a diamine and a polycarboxylic acid, The diamine is dimer diamine, The polymer unit (B) of the ethylenically unsaturated monomer has an epoxy group, and the crosslinking agent (D) has a phenolic hydroxyl group, or The curable resin composition, wherein the polymer unit (B) of the ethylenically unsaturated monomer has a phenolic hydroxyl group, and the crosslinking agent (D) has an epoxy group.
2. 2. The curable resin composition according to claim 1, wherein the amount of the polymer unit (B) of the ethylenically unsaturated monomer is 10 to 50 mass % based on the total mass of the block polymer (C).
3. 3. The curable resin composition according to claim 1, wherein the glass transition temperature of the polymer unit (B) of an ethylenically unsaturated monomer is higher than the glass transition temperature of the polyimide unit (A).
4. 4. The curable resin composition according to claim 1, wherein the polymer unit (B) of the ethylenically unsaturated monomer has a phenolic hydroxyl group.
5. The curable resin composition according to any one of claims 1 to 4, which is an adhesive.
6. A laminate comprising a layer made of the curable resin composition according to any one of claims 1 to 5 and a substrate.
7. 7. The laminate according to claim 6, wherein the substrate is a copper foil and / or an insulating sheet.
8. 8. A thermoset laminate obtained by heating the laminate according to claim 6 or 7 to thermally cure a layer made of a curable resin composition in the laminate.
9. 9. The thermosetting laminate of claim 8 which is a printed wiring board.
Citation Information
Patent Citations
Phase controller of cleaning device
JP1986088788A
Polyimide, adhesive, film-like adhesive, adhesion layer, adhesive sheet, copper foil with resin, copper-clad laminate, printed wiring board, and multilayer wiring board and method for producing the same
JP2018168369A
Thermosetting adhesive sheet, and use thereof
JP2019099583A
New block polymer, resin composition and sheet
JP2020063344A
Poly(meth)acrylate-block-polyimide-block-poly(meth)acrylate copolymers with (meth)acrylate functionality, their preparation and use
JP2020517769A